Exploring Identity and Social Dynamics in Chimamanda Ngozi Adichie's Americanah (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Chimamanda Ngozi Adichie's novel Americanah intricately weaves a narrative tapestry exploring themes of identity, race, and belonging. Through the protagonist, Ifemelu's journey from Nigeria to the United States and back, the novel provides profound insights into the complexities of identity formation in a globalized world. This research paper delves into Adichie's exploration of identity construction, particularly focusing on how societal structures, cultural contexts, and personal experiences shape individuals' understanding of themselves and their place in the world. By analyzing key characters, narrative techniques, and socio-political contexts, this paper aims to unravel the multifaceted layers of identity portrayed in the novel and its implications for contemporary discussions on race, immigration, and social dynamics.